The AI Paradox: Does Artificial Intelligence Truly Reduce Healthcare Costs? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2024)
The AI Paradox: Does Artificial Intelligence Truly Reduce Healthcare Costs? The global healthcare system is grappling with an unsustainable rise in expe...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Medical Ethics; Clinical Decision Support